2018
DOI: 10.1080/20009666.2018.1479617
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial aetiology for non-uremic calciphylaxis: a case report

Abstract: Calciphylaxis is commonly associated with end-stage renal disease patients on haemodialysis. We present a rare case of calciphylaxis in a non-uremic patient. The diagnosis was made clinically and confirmed with skin biopsy showing calcification of the dermal and subcutaneous tissues in the von Kossa stain. We believe that the combination of uncontrolled diabetes mellitus, a non-functioning paraganglioma and vitamin D deficiency in a susceptible female patient was responsible for causing calciphylaxis in our pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Most of the studies reported multiple conditions 18 (33.96 %) [8,5,9,10,11,[12][13][14]6,15,16,17,1819,20,21,22], [7]; define herein as patients suffering from more than two morbidities were assembled in multiple conditions. Other morbidities among the included studies were warfarin induced (7.54 %) [23,24,25 1).…”
Section: Fig 1 An Overview Of the Approach For Doing A Literature Searchmentioning
confidence: 99%
“…Most of the studies reported multiple conditions 18 (33.96 %) [8,5,9,10,11,[12][13][14]6,15,16,17,1819,20,21,22], [7]; define herein as patients suffering from more than two morbidities were assembled in multiple conditions. Other morbidities among the included studies were warfarin induced (7.54 %) [23,24,25 1).…”
Section: Fig 1 An Overview Of the Approach For Doing A Literature Searchmentioning
confidence: 99%